Technical Guidance For Implementation Cloud Computing Technology For Support Learning Network Computers At Cipta Insani Vocational School Independent - Nuraini Purwandari; Boy Firmansyah; Rr Ayanti Kristantini; Hilman Jihadi; Harjo Baskoro; Ardi Kurniawan (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
The purpose of community service is give guidance technical about implementation cloud computing technology in support learning network computers at Cipta Insan Vocational School Independent . Activities This covering socialization , training practical , and study designed case​ For increase teacher and student understanding about cloud computing. The results of activity This show improvement significant in understanding participant about cloud computing concepts and applications , as well as integration a number of module learning with technology In addition , students​ show improvement skills practical in using cloud platforms to project network computer . Feed come back Participants also reflected mark positive from activity this , which is expected can contribute to the improvement quality education in the digital age. The success of this program shown with activity all participants and enthusiasts participant do discussion and results questionnaire satisfaction show by 90.50% of participants satisfied with existence training This Because can increase understanding as well as ability practical student about Cloud Computing.